Cu-releasing bioactive glass/polycaprolactone coating on Mg with antibacterial and anticorrosive properties for bone tissue engineering. (26th October 2017) - Yang, Yuyun; Zheng, Kai; Liang, Ruifang; Mainka, Astrid; Taccardi, Nicola; Roether, Judith A; Detsch, Rainer; Goldmann, Wolfgang H; Virtanen, Sannakaisa; Boccaccini, Aldo R
Abstract: Bioactive glass nanoparticles containing copper (Cu-BGNs) were introduced into polycaprolactone (PCL) coating systems to improve the bioactivity, antibacterial properties, and corrosion resistance of vulnerable magnesium matrices under physiological conditions. The influence of different amounts of Cu-BGNs in PCL coatings was thoroughly investigated in determining the wettability, electrochemical properties, and antibacterial effects against Staphylococcus carnosus and Escherichia coli, as well as their cyto-compatibility. Cu-BGNs were observed randomly scattered in PCL coatings. Increasing the concentration of Cu-BGNs resulted in a slight decrease of the water contact angle, and a reduction in anticorrosion properties of the Cu-BGN composite coatings. Yet higher Cu-BGN content in coatings led to more calcium phosphate formation on the surface after 7 days of immersion in Dulbecco's modified Eagle's medium, which was confirmed by Fourier-transform infrared spectroscopy and x-ray photoelectron spectroscopy. The growth of S. carnosus and E. coli was inhibited by Cu 2+ ions released from the Cu-BGN coatings. In addition, both direct and indirect cyto-compatibility experiments showed that the viability and proliferation of MG-63 cells on Cu-BGN coatings were highly increased compared to pure magnesium; however, an additional increase of Cu-BGN concentration showed a slight decrease of cell proliferation and cell activity. In summary, Cu-BGN/PCL composite coatings impart magnesium-based biomaterials with antibacterial and anticorrosive properties for clinical applications.